MENGUKUR KINERJA KEUANGAN DENGAN PENDEKATAN METODE RGEC PADA BANK PEMBANGUNAN DAERAH DI PULAU SULAWESI PERIODE 2019-2023 - Luciana, Vita; Permata Indah, Djunita; Haryono, Haryono (Penerbit Lafadz Jaya, 2025)
The objective of the study is to evaluate the financial health level of Regional Development Banks (BPD) in the Sulawesi region during the 2019–2023 period. The study uses a financial institution health assessment approach. This assessment is needed to assess the feasibility and stability of banks in carrying out their financial intermediation functions. The quantitative descriptive system used uses data from the annual financial reports of Bank Sulselbar, Bank Sulutgo, Bank Sulteng, and Bank Sultra. The results of the analysis state that all financial institutions have an impressive level of health because the aspects of Capital (CAR) and Income (ROA, NIM), but several banks are in the unhealthy category related to the Risk Profile, especially in the comparison of Loans to Third Party Funds. In a situation of Good corporate leadership, it shows that all banks are considered healthy based on their independent assessments, although some are still quite healthy in terms of Return on Equity (ROE). Overall, this study indicates that the majority of BPDs in Sulawesi describe positive financial capabilities so that they are able to maintain operational stability, although there are several indicators that need to be improved. It is hoped that these findings can help policy makers, bank management, and further researchers in evaluating and improving the financial performance of banking in the region.